Cinematic Learning-Teaching: The Role of English Movies in Vocabulary Acquisition for EFL Learners - Juhansar, Juhansar; Budiarti, Budiarti; Shahrin Bin Hashim; Reriansyah; Sihole, Irene Gabriella (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2024)
English movies present an engrossing and immersive experience for language learners, making them an appealing medium for expanding vocabulary. This study investigates learners’ viewing habits and preferences for English movies, as well as the perceived influence of these mediums on vocabulary acquisition, efficient viewing techniques, and extra advantages beyond vocabulary building. A questionnaire that combines quantitative and qualitative data collection techniques is used in a descriptive survey approach. Descriptive statistics, cross-tabulation, theme analysis, and content analysis are all used in the data analysis process to give a thorough picture of how English movies aid in vocabulary acquisition for EFL learners. The results indicate that most learners regularly watch English movies, with action movies being the most popular genre. Most participants watch English movies for an hour on average, and all respondents concur that viewing movies helps people learn new words. Most learners prefer to watch movies with subtitles because they help with vocabulary development and understanding. The results also emphasize the wider advantages of seeing English movies, such as increased motivation, better English proficiency in speaking, listening, and pronunciation, and a deeper comprehension of cultural nuances and English use in everyday situations. This current study recommends the need for greater investigation into the wider effects of English movies on English proficiency and pedagogical strategies to maximize their application in English learning-teaching environments.